IMPACT DU CONTROLE DE L’ASSEMBLEE PROVINCIALE SUR LA GESTION DE FINANCES PUBLIQUES DE LA PROVINCE ORIENTALE (RDC) DE 2007-2015 - LIMENGO , Dieudonné BARUTI; YILA , Clément ATSIDRI (IJRDO - Journal of Business Management, 2019)
The present study on the impact of the control of the provincial assembly on the public finance management in Oriental Province in RDC enters in the setting of decentralization as one of pillars of the local governance and this decentralization has been instituted by the constitution of February 18th, 2006 as modified January 20th, 2011 and the Law n°08/012 of July 31th, 2008. Provinces are a political and administrative component of the RDC. They enjoy the free administration and the autonomy of the management of their economic, human, techniques and financial resources. The provincial assembly must exercise the control on the management of public finances of the province carries out by the provincial government.  It is necessary to note that, during the period under exam, the provincial assembly has experienced this control but it is often inefficient. This inefficiency of the control of the provincial assembly is owed to certain factors, of which the institutional weakness, the human resource problem and the provincial deputy capacity to make this work as well as the lack of transparency of the provincial government.